Ferrimagnetism in manganese-rich gallium and aluminium spinels due to mixed valence Mn2+–Mn3+ states. Issue 8 (7th February 2018) - Bekheet, Maged F.; Schlicker, Lukas; Doran, Andrew; Siemensmeyer, Konrad; Gurlo, Aleksander
Abstract : A novel synthesis methodology was applied for obtaining ferrimagnetic Mn1+ x M(IIIA)2− x O4 spinels (M(IIIA) = Ga 3+ and Al 3+ ) with small optical band gaps due to mixed valence Mn 2+ –Mn 3+ states. Abstract : Stoichiometric (MnGa2 O4 and MnAl2 O4 ) and Mn-rich (Mn1.3 Ga1.7 O4 and Mn1.4 Al1.6 O4 ) spinels with a small inversion degree (0.14–0.21) were obtained via a co-precipitation route followed by calcination of the as-synthesized coprecipitates at 700–1000 °C under different gas atmospheres (air, N2 or argon). In situ synchrotron XRD at elevated temperatures reveals the conditions for synthesizing phase-pure materials. The stoichiometry of the samples is confirmed by inductively coupled plasma optical emission spectrometry as well as by structure refinement of neutron diffraction data of phase-pure specimens. XANES characterization reveals the average oxidation state of manganese to be +2.2 and 2.3 in Mn1.3 Ga1.7 O4 and Mn1.4 Al1.6 O4 spinels, respectively. The mixed Mn 2+ –Mn 3+ valence states are responsible for the ferrimagnetic properties of Mn1.3 Ga1.7 O4 and Mn1.4 Al1.6 O4 samples below 48 and 55 K, respectively, as well as for a smaller optical bandgap when compared to stoichiometric spinels.